Anatomical and Technical Reappraisal of the Pallidothalamic Tractotomy With the Incisionless Transcranial MR-Guided Focused Ultrasound. A Technical Note - Gallay, Marc N.; Moser, David; Federau, Christian; Jeanmonod, Daniel (Frontiers in Surgery, 2019)
Background: MR-guided focused ultrasound (MRgFUS) offers new perspectives for safe and efficient lesioning inside the brain. The issue of target coverage remains primordial and sub-optimally addressed or solved in the field of functional neurosurgery. Objective: To provide an optimized planning and operative strategy to perform a pallidothalamic tractotomy (PTT) in chronic therapy-resistant Parkinson's disease (PD) with the technology of MRgFUS. Methods and results: Histological sections and maps from 6 human brain hemispheres were analyzed and outlines of the pallidothalamic tract on Myelin-stained sections were drawn and superimposed. We determined a standardized PTT target coverage characterized by 5 to 7 preplanned target lesion sub-units of 1.5 × 1.5 × 3.0 mm, which were placed using focal point displacements and shortest possible times, under thermal dose control. Conclusion: We hereby present our current approach to the MRgFUS PTT on the basis of a histological reappraisal and optimized heat application to the pallidothalamic tract in the H1 field of Forel.